Evaluation of residual stresses in multipass dissimilar butt-welded of SS316L to Inconel625 using FEA - Vemanaboina, Harinadh; Edison, G; Akella, Suresh (International Journal of Engineering and Technology, 2018)
In the present analysis, thermo-mechanical process was employed to study the thermal and structural behaviour of three pass dissimilar butt-joints of SS316L to Inconel625 alloys. The temperatures evolution and residual stresses developed in the weldments were reported for each pass in the transverse direction to fusion zone. The Ansys Parametric Design Language (APDL) used for modelling and analysis of welding process with the double ellipsoidal heat source. The temperature dependent thermal and mechanical properties used in the simulation process. The residual stress is compressive in SS316L side compared to Inconel 625. The residual stress is within the yield limits of both base materials. The results obtained from the simulation process will be helpful for maintaining the structural integrity.Â